2020
DOI: 10.11606/s1518-8787.2020054002545
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin D play a role in the management of Covid-19 in Brazil?

Abstract: The study discusses the possible role of adequate vitamin D status in plasma or serum for preventing acute respiratory infections during the Covid-19 pandemic. Our arguments respond to an article, published in Italy, that describes the high prevalence of hypovitaminosis D in older Italian women and raises the possible preventive and therapeutic role of optimal vitamin D levels. Based on literature review, we highlight the findings regarding the protective role of vitamin D for infectious diseases of the respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
3
14
0
10
Order By: Relevance
“…Hence, low 25(OH)D level was identified as independently associated with the likelihood of COVID‐19 infection. This finding is in agreement with the results of other studies [5,7,9–15,19,30–42]. Further, reduced risk of acute respiratory tract infection following vitamin D supplementation has been reported [43,44].…”
Section: Discussionsupporting
confidence: 94%
“…Hence, low 25(OH)D level was identified as independently associated with the likelihood of COVID‐19 infection. This finding is in agreement with the results of other studies [5,7,9–15,19,30–42]. Further, reduced risk of acute respiratory tract infection following vitamin D supplementation has been reported [43,44].…”
Section: Discussionsupporting
confidence: 94%
“…An adjustment in Vitamin D levels in the intake would also strengthen the immune system. [130][131][132][133][134][135][136] Plant-based fiber has prebiotic effects such as promoting the growth of bacteria that are associated with health benefits, such as Bifidobacterium and Lactobacillus spp. Moreover, reduce potential pathogens such as Clostridium spp.…”
Section: Changes In the Gut Microbiota Composition Through Diet To Dementioning
confidence: 99%
“…Two May 2020 Centre for Evidence-Based Medicine rapid reviews concluded, without discussing any of the recent studies, that there is no evidence to support a role for vitamin D in prevention or treatment of COVID-19 or the cytokine storm (45,55). Alarmed by the media response to a literature review suggesting a link between COVID-19 and vitamin D, two Brazilian medical associations jointly published a note stating that vitamin D supplements are only approved for bone health (56)(57)(58). The high mortality rates among minorities are providing momentum for various public health program expansions, which could diminish if vitamin D deficiency, rather than access to care and economic disparities, were found to be even a partial explanation (59)(60)(61)(62).…”
Section: The Vitamin D Debatementioning
confidence: 99%
“…Current increased "stay at home" regulations and increased boredom and stress can be expected to result in eating patterns which increase obesity and the comorbidities with which it is associated (189). In part because vitamin D is fat-soluble, obese individuals have increased daily vitamin D intake requirements and are often deficient (25,34,57,91,175,190,191). In addition, vitamin D deficiency causes the body to store more fat by increasing parathyroid hormone levels (192).…”
Section: Risk For Severe Covid-19 Parallels Risk For Vitamin D Deficimentioning
confidence: 99%